การวิจัยและพัฒนานวัตกรรมการเรียนรู้เพื่อพัฒนาทักษะในศตวรรษที่ 21 ของผู้เรียนอาชีวศึกษา - Thaithae, Ittiwat; Akakul, Theerawut (Ubon Ratchathani Journal of Research and Evaluation, 2024)
This article presents the application of research and development for the development of learning innovations to develop 21st century skills of vocational students. This aims to develop students to have quality according to professional and international standards, and have work skills that meet the needs of the workplace. Research and development has a systematic research plan, a design process, and continuous improvement and development in a cycle until the desired results are obtained, which can be verified and are reliable. Therefore, it can effectively develop and solve problems in learning management that meet the needs of students, educational institutions, and workplaces.